(untitled) (Journal of Asian Development Studies, 2025)
Literature is scarce regarding the mental health outcomes of caregivers of individuals with neurocognitive and neurodevelopmental disorders, particularly when comparing caregivers of both disorders, specifically in Pakistan. This study aims to fill this gap, provide implications and policy recommendations, and contribute to future research. The mental health outcomes are operationalized as depression, anxiety, and stress. A cross-sectional correlational design and purposive sampling were used to collect data from caregivers of children with neurodevelopmental disorders (under 18) and caregivers of individuals with neurocognitive disorders (at least 65 years old). The study included 210 participants: 100 caregivers of individuals with neurodevelopmental disorders and 110 caregivers with neurocognitive disorders, with a mean age of 37.78 and a standard deviation of 9.62. The Depression Anxiety Stress Scale (DASS-21) was used to measure depression, stress, and anxiety. Findings revealed a significant positive relationship between stress, anxiety, and depression. An independent samples t-test showed that caregivers of individuals with neurodevelopmental disorders scored significantly higher on depression, anxiety, and stress than caregivers of individuals with neurocognitive disorders. The study discussed these findings about relevant literature and provided implications and policy recommendations for the social welfare of caregivers of individuals with neurodevelopmental and neurocognitive disorders.